2018
DOI: 10.1155/2018/1594182
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Assessment of Renal and Liver Function among Preeclamptics in Lagos Metropolis

Abstract: Objectives Preeclampsia is a pregnancy specific syndrome. Studies have shown that preeclampsia has multiorgan dysfunction effects. This study evaluated biomarkers of renal and liver function among preeclamptic Nigerian women. Study Design This was a cross-sectional study conducted among 49 preeclamptic women and 50 normotensive healthy pregnant women. Method The baseline data comprising age, gestational age, and blood pressure were obtained. Venous blood and spot urine samples were collected from each particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 43 publications
8
19
1
2
Order By: Relevance
“…In a Nigerian population, Okonkwo and colleagues previously founda mean uric acid level of 6.05mg/dl in thirdtrimester normal pregnancies, which is comparable with the present study [25]. In pre-elamptic pregnancies, Ekun et al, Pramanik et al, Deshpande et al, Kasraeian et al respectively reported mean uric acid levels of 6.69, 6.27, 6.21, 6.20mg/dl comparable to the present study [28][29][30][31].…”
Section: Discussionsupporting
confidence: 90%
“…In a Nigerian population, Okonkwo and colleagues previously founda mean uric acid level of 6.05mg/dl in thirdtrimester normal pregnancies, which is comparable with the present study [25]. In pre-elamptic pregnancies, Ekun et al, Pramanik et al, Deshpande et al, Kasraeian et al respectively reported mean uric acid levels of 6.69, 6.27, 6.21, 6.20mg/dl comparable to the present study [28][29][30][31].…”
Section: Discussionsupporting
confidence: 90%
“…New onset proteinuria was defined as 300 mg or more per 24 h urine collection (or this amount extrapolated from a timed collection) or protein/creatinine ratio of 0.3 mg/dl or more or dipstick reading of 2+ (used only if other quantitative methods were not available) [ 52 , 53 ]. In the absence of proteinuria, new-onset hypertension with the new onset of any of the following were taken into account: (1) thrombocytopenia (platelet count less than 100 × 10 9 /L), (2) renal insufficiency (serum creatinine concentrations greater than 1.1 mg/dl or doubling of the serum creatinine concentration in the absence of other renal disease), and/or (3) impaired liver function (elevated blood concentrations of liver transaminases to twice the normal concentration) [ 54 , 55 , 56 ]. Other symptoms included pulmonary edema, new-onset headache unresponsive to medication, and those not accounted for by alternative diagnoses or visual symptoms [ 18 , 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…Diagnosis of PE was based on the International Society for the Study of Hypertensive Disorders in Pregnancy (ISSHP) classification [1] in terms of diastolic blood pressure of 90 mm Hg or above or systolic blood pressure of 140 mm Hg or above, and proteinuria of 2+ in dipstick. In the case of no proteinuria, the criteria of thrombocytopenia, hemolysis, renal insufficiency, impaired liver function, or pulmonary edema were applied [1,[6][7][8][9].…”
Section: Preeclampsia (Pe) Fetal Growth Restriction (Fgr) and Pretermentioning
confidence: 99%
“…Preeclampsia (PE) is a major pregnancy complication associated with high morbidity and mortality [1][2][3][4][5]. Diagnosis of PE is made if a previously normotensive woman develops hypertension after 20 weeks gestation accompanied by proteinuria [6], and/or thrombocytopenia [7], elevated liver enzymes or hemolysis, along with the occasional involvement of other organs, mainly the cardiovascular system, the eyes, and the brain [1][2][3][4][5][6][7][8][9]. National societies of Maternal and Fetal Medicine and individual medical centers have established protocols to guide proper clinical management for saving the life of the mother and fetus/neonate and reducing morbidity [3,4].…”
Section: Introductionmentioning
confidence: 99%